The correlation of inner strength and health promoting behaviors in women with heart failure - hosseini, Meimanat; rashidi, Sakineh; vasli, Parvaneh; shahsavari, Soodeh (Advances in Nursing & Midwifery, 2016)
Abstract Background Health promoting behaviors are appropriate actions to promote health and prevent further decompensation due to heart failure. Inner strength is a factor of psychological health and well- being and therefore is a dynamic element in holistic recovery. The aim of this study was to determine the correlation of inner strength and health promoting behaviors in women with heart failure referring to hospital affiliated with Beheshti University of Medical Sciences in 2013. Materials and methods In this descriptive-Correlation Study, 145 women with heart failure referring to hospital affiliated with Shaheed Beheshti Medical University were selected by convenience sampling method. A 3-part questionnaire including demographics, inner strength questionnaire and Health-promoting lifestyle profile II was used for data collection. Data were analyzed with SPSS 20. Finding There was significant correlation between inner strength and health promoting behaviors dimensions and health promoting behaviors in general (p<0.001) as well as between all dimensions of inner strength (except knowing and Searching dimension with physical activity, connectedness dimension with health responsibility and connectedness dimension with physical activity) (p<0.01). Conclusion There is significant correlation between inner strength and health promoting behaviors of women with heart failure. Therefore, attention to enhancement of inner strength by nurses seems necessary to improve the health in women with heart failure. Keywords: Inner strength, Health promoting behaviors, Women, Heart failure